Analysis of effective sentences in the scientific papers of the students of Politeknik Negeri Bali - I Nyoman Mandia; I Nyoman Sukra (English, 2018)
This study aims to determine the use of Indonesian sentence patterns and the level of effective use of Indonesian sentence in scientific papers of students of the Diploma Program III of Politeknik Negeri Bali. The method in this research is a qualitative method, while the method of collecting data in the form of documentation with qualitative descriptive analysis. From the results of effective sentence analysis can be mentioned: (1) the use of effective sentences in scientific papers students diploma program III shows the average value in each sample of 73.85, the highest value of 90.00 and the lowest of 43.48; (2) the use of effective sentences for each department indicates: Accounting Department 80,53, Civil Engineering Department 76.07, Administration Department 75.80, Tourism Department 72.44, Electrical Engineering Department 71.95, and Mechanical Engineering Department 71.22; (3) the results of the study in each study program group can be described: Accounting Department 80.53, UPW 79.70, Information Systems Department 79.04, Mechanical Engineering Department 77.70, Civil Engineering Department 76.07, Administration Department 75.80, Hospitality 67.14, Electrical Engineering Department 66.04, and TPTU 64.75; (4) and the results the study of effective sentence type indicate errors such as parallelism 142, efficiency 114, correspondence 61, austerity and parallelism 15, parallelism and correspondence 15, and logicality 3. Based on the results of this study, it can be concluded that the ability of effective sentences of the students is quite good.